Effect of cultivar selection on symbiotic nitrogen fixation and yield traits of pea cultivars in intercropping with wheat - Chathuranga De Silva; Pramod Rathor; Thomas D. Warkentin; Hari P. Poudel; Malinda S. Thilakarathna (Discover Agriculture)
Abstract In recent decades, agricultural practices have shifted from diverse cropping systems to monocropping, leading to soil degradation, nutrient depletion, and reduced biodiversity, which threaten long-term productivity and ecosystem sustainability. This study aimed to explore how legume cultivar selection influences pea (Pisum sativum L.)-wheat (Triticum aestivum L.) intercropping, focusing on symbiotic nitrogen (N) fixation, yield, seed N, and land productivity. A greenhouse experiment was conducted using various pea cultivars that were released in different decades [Century (1960), Trapper (1970), CDC Golden (2002), CDC Amarillo (2012), and CDC Spectrum (2016)] under monocropping and intercropping with wheat to evaluate the yield parameters and symbiotic N fixation capabilities of pea. The old, long-vined pea cultivars (Century and Trapper) had higher seed dry weight (62.9–66.3%), number of pods (82.7–100%) and number of seeds (126.9–163.5%) than the newer, moderate vine length cultivars (CDC Golden, CDC Amarillo and CDC Spectrum) under intercropping. On the other hand, the companion wheat crop had a greater yield (29.8–69.9%) and seed N (31.1–65.5%) when intercropped with the newer pea cultivars. Intercropping enhanced N fixation (0.7–7.5%) in peas across cultivars; however, the older cultivars contributed more to the overall system’s N fixation and N carry-over compared to the newer cultivars. While the harvest index, land equivalent ratio (LER), and N-based LER (LERN) of intercropped wheat were not significantly higher than mono-cropped wheat, the increased partial LER and LERN for wheat highlight intercropping benefits. Overall, newer pea cultivars enhanced pea-wheat intercropping by improving productivity and resource efficiency, highlighting the importance of legume cultivar selection in intercropping. Graphical abstract